Indirubin may be involved in the pathogenesis of psoriasis by targeting MAPK14 - Shougang LIU; Fanghua LIU; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the target of indirubin in psoriasis, and to elucidate the possible effect of indirubin on psoriasis through MAPK14. Methods The GSE30999 and GSE78097 psoriasis datasets downloaded from the Gene Expression Omnibus (GEO) database were used as training and validation sets, respectively. The differentially expressed genes were screened, and their biological functions and pathways were analyzed. Intersections with indirubin target genes were used to obtain differentially expressed indirubin target genes. Meanwhile gene correlation was analyzed and differential gene expression was verified. LASSO and Cox regression model were used to screen the best target genes for indirubin. Molecular docking of indirubin was performed to analyze the structural relationship. Results A total of 8 indirubin target genes were found in the GSE30999 dataset, which were differentially expressed compared with the control group. Seven genes had high diagnostic value (AUC>0.8), and one gene had low diagnostic value (AUC>0.6). GO and KEGG enrichment analyses showed that the eight indirubin target genes were mainly related to cell aging, chemical carcinogenic receptor activation, lipid and atherosclerosis, acute myeloid leukemia, and AGE-RAGE signaling pathways in diabetic complications. The best target gene of indirubin, MAPK14 gene, was screened by LASSO and Cox regression model. Molecular docking suggested that indirubin was tightly bound to MAPK14. Conclusion Indirubin may be involved in the regulation of the pathogenesis and treatment of psoriasis through MAPK14.